Single miller capacitor frequency compensation techniques: Theoretical comparison and critical review. (11th February 2022) - Grasso, Alfio Dario; Marano, Davide; Palumbo, Gaetano; Pennisi, Salvatore
Abstract: This paper presents a systematic analytical comparison of the single‐Miller capacitor frequency compensation techniques suitable for three‐stage complementary metal–oxide–semiconductor (CMOS) operational transconductance amplifiers (OTAs). The comparison is carried out with the aid of a figure of merit that expresses a trade‐off among gain‐bandwidth product, load capacitance, and total transconductance, for equal values of the phase margin. The results found can be used before the transistor‐level design step and provide useful guidelines for the optimization of the small‐signal performance. Simulations by using a 65‐nm standard CMOS technology confirming the effectiveness of the theoretical comparison for 10 different OTA topologies are also provided. Abstract : We present a systematic analytical comparison of the single Miller capacitor frequency compensation techniques suitable for three‐stage CMOS operational transconductance amplifiers (OTAs). The results found can be used before the transistor‐level design step and provide useful guidelines for the optimization of the small‐signal performance.